DEFINING AND ESTIMATING UNDERGROUND AND INFORMAL ECONOMIES: THE NEW INSTITIONAL ECONOMICS APPROACH - Edgar L. Feige
A taxonomy of underground economies is elaborated based on the new institutional approach to economic development. Members of formal sectors confront different sets of transformation and transaction costs than do members of informal sectors and these differences are regarded as crucial to the development process. The paper distinguishes illegal, unreported, unrecorded and informal economies and examines the conceptual and empirical linkages among them. Alternative micro and macro methodologies for measuring underground activities are reviewed and evaluated including census and survey procedures, discrepancies and monetary methods. To be published in World Development, Vol 18, No 7, 1990.Underground, unrecorded, unreported, informal, illegal, unobserved, hidden, shadow economy, transaction costs, monetary methods.